Revestimento de polietileno de alta densidade (pead) como sistema de proteção contra corrosão em oleodutos no RN - Araújo, Thiago Ticiano Aires de (Universidade Federal Rural do Semi-Árido, 2019)
Brazil's oil, gas and derivatives supply structure, interconnected with production sources, refineries and consumption centers, is based mainly on the country's pipeline network. To date, much of this network is operated by Petrobras or Transpetro, in which a highly significant portion (around 77%) of its extension consists of pipelines with more than 20 years of operation. Studies have shown that transportation pipelines in operation in the country present serious problems of internal and / or external corrosion and deposit formation, both organic and inorganic. As a result of the corrosive process, there is a reduction in the thickness of the duct walls, possible appearance of localized attack in condensation and water retention regions and the formation of large amount of solid residue due to the large surface area of the ducts that come into contact with the flow. The extent and severity of these problems are related to the type of product transported, operating conditions and location, implying periodic maintenance. The suspension of maintenance services causes numerous damages, among them the interruption of transmission services and the environmental problems that occur due to leaks in the pipelines. In Brazil, an internal lining system has been used for pipelines to conduct oil, gas, water, etc., made of high density polyethylene (HDPE) pipes to protect them against corrosion and abrasion, called Liner. The present work aims to present the main characteristics of High Density Polyethylene (HDPE) coatings and their cost relation when compared to the construction of a new pipeline and transportation via tank trailers (1, 2, 3 and 4 years). It has been observed that after 2 years hauling production through trailers, the expense of this drawback is equivalent to the cost of rehabilitating the pipeline with the insertion of the expanded HDPE liner for both the AB and CD pipelines and after 3 (three) years, the costs of transporting the trailer exceed the investment for liner insertion, while at the fourth year the values involved are practically equivalent to the cost of manufacturing a new steel pipe with the same characteristics as the previous one.
Artigo Acadêmico
Keywords: Corrosão; Revestimento; PEAD; Dutos; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA